A competency-based approach to critical care education - Li-Liang Chuang; Ming-Chen Hsieh (Tzu Chi Medical Journal)
The medical education environment is rapidly changing. Competency-based medical education (CBME) is a great advance, but operationalizing competencies for teaching and assessment is problematic. Entrustable professional activities (EPAs) can revitalize CBME by connecting competencies to practice, creating flexibility in programs. CBME requires and deepens the nature of workplace-based assessments. It is important to use EPAs to verify residents' ability to care for critically ill patients unsupervised in simulation education.